Seismotectonic analyses of Karachi Arc, Southern Kirthar Fold Belt, Pakistan: Seismotectonic analyses of Karachi Arc, Southern Kirthar Fold Belt, Pakistan - Nabi, Ahmad; Liu, Xiaodong; Gong, Zhijun; Pervaiz, Khalid; Ali, Abbas; Khalil, Umair (International Journal of Economic and Environmental Geology, 2019)
In this study geomorphological and seismotectonic analyses were carried out in Karachi arc area, southern Pakistan to locate relatively safe areas from earthquakes disasters. Karachi arc is the southern extremity of the Kirthar mountain chain that occupies a major part of southern Pakistan and is comprised of a number of narrow, elongated mountain ranges, i.e. Laki, Kirthar, Khud, Pab and Mor ranges. Based on geomorphological and seismotectonic analyses Karachi arc area has been divided into three parts. These parts are northern, frontal and southern part. The northern part of Karachi arc is seismically active where minor to moderate (3-5.9Mb) earthquakes occurred. Some basement structures in Sehwan area seem to be still active and affected by the present-day transpressional stress field. The frontal part of Karachi arc is also active as manifested by the existence of active faults in Jhimpir, Surjan and Meting areas. These embryonic structures in the eastern part of the Arc are indicators of active deformation of Karachi arc. Presently the active deformation is taking place in frontal and northern parts of the arc, while the southern part that has experienced deformation prior to Quaternary time is inactive and is relatively stable geoblock. The instrumental and historic seismicity record of the adjoining areas of Karachi arc show that the area has experienced light to moderate seismic events (4-5.9) with occasional occurrence of strong and major earthquakes. Any major or strong event in Katch rift zone, Makran subduction zone and Ornach-Nal fault zone may cause intensity of VII to VIII in Karachi arc area as well as Karachi city of environmental seismic intensity scale 2007.